2014
DOI: 10.1002/ajhb.22526
|View full text |Cite
|
Sign up to set email alerts
|

Lower hemoglobin levels in first time mothers from Cebu, Philippines

Abstract: Low hemoglobin levels of primiparous women in this sample might indicate increased nutritional stress associated with first pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Research has suggested that women do in fact recover iron lost to pregnancy during the postpartum period, although the recovery of iron lost may be incomplete (Miller, ). The verdict is still out as to how this recovery occurs—whether it reflects passive absorption of iron, or is mediated by some sort of iron recovery process (Dewey, ; Yoon et al, ). Evidence from studies of hepcidin levels during pregnancy and after pregnancy shows that iron absorption is not upregulated during the postnatal period (van Santen et al, ), suggesting the stronger likelihood of a passive absorption process.…”
Section: Reproductive Iron Withholding: the Gestation‐lactation Iron mentioning
confidence: 99%
See 2 more Smart Citations
“…Research has suggested that women do in fact recover iron lost to pregnancy during the postpartum period, although the recovery of iron lost may be incomplete (Miller, ). The verdict is still out as to how this recovery occurs—whether it reflects passive absorption of iron, or is mediated by some sort of iron recovery process (Dewey, ; Yoon et al, ). Evidence from studies of hepcidin levels during pregnancy and after pregnancy shows that iron absorption is not upregulated during the postnatal period (van Santen et al, ), suggesting the stronger likelihood of a passive absorption process.…”
Section: Reproductive Iron Withholding: the Gestation‐lactation Iron mentioning
confidence: 99%
“…A study of Nigerian women also found no relationship between parity and hemoglobin and ferritin levels, despite high rates of anemia during pregnancy (Adediran et al, ), and a study in east Sudan found that primigravidous women were more likely to be anemic than other women during pregnancy (although anemia during pregnancy rates were high at 58.4%; Mohamed et al, ). Hemoglobin levels were also lower among primiparous women compared to multiparous women in an age‐matched cohort of Filipino women, although mean hemoglobin levels were not in the anemic range for women of any parity (Yoon et al, ).…”
Section: Long‐term Reproductive Effort and Ironmentioning
confidence: 99%
See 1 more Smart Citation